Dimensões do agir docente em relatos reflexivos de bolsistas PIBID - Dantas, Giuseppe Andrew Ferreira (2019)
Teaching education is a considerable field of research that has been seriously discussed in matters of the teacher's work, language practices and teaching-learning contexts, in which idiosyncrasies are approached at education courses. Belonging to a collective work group is a crucial factor in the teacher's professional identity (BORGES, et al., 2015; LIMA, SILVA, 2017; MATEUS et. al., 2013), that is because formative spaces offer a more significant articulation between theory and practice, thus valuing both human subjectivities and practices lived and learned in the dialogical partnership between school and university. Hence, situated in the contemporary and transdisciplinary Applied Linguistics (MOITA LOPES, 2006; 2008; CELANI, 2005; 2016; RAJAGOPALAN, 2006, among others), this master degree thesis investigates the dimensions of acting according to the perspective of undergraduate students at PIBID/Letras-Inglês subproject of UFPB/Campus I, taking into account the teaching act of these professional in accordance with motives, intentions and resources of acting. In order to understand the formation context of the subproject, it was analyzed a set of 20 reflective reports of two PIBID scholars at practicing in 2017. This current study is supported by the concept that these teachers are the real theorists of their practice, and their narratives reveal pretty much about the representation of their work (BORTONI- RICARDO, 2008, MEDRADO, 2012). Besides, it is understood that reflective writing (BURTON, 2009; REICHMANN, 2013) is a source of development in terms of language, since it legitimizes the voice of the scholars in the reflective journal as catalyst genre that allows a continuous process of integration and negotiation of senses (SIGNORINI, 2006). These reports were studied and analyzed from the theoretical- methodological framework of Sociodiscursive Interactionism (BRONCKART, 1998; 1999; 2006; 2008), focusing on the types of discourses, enunciative modalizations and, above mostly, on the Semiology of Acting (BRONCKART, MACHADO). , 2004; BRONCKART, 2006; MACHADO, BRONCKART, 2009), more precisely regarding to the mobilization of the motivational, intentional and resources for acting dimensions, in both individual and collective plans of analysis. For the purpose of understanding teaching as work (MACHADO, 2007), this research adopts the epistemological concepts of Work Sciences and Clinic of Activity, which explain work as a human activity of social and psychological order that constitutes the professional gender and the style of the worker (AMIGUES, 2007; CLOT, 2007; 2010; FAÏTA, 2004, among others). Therefore, in conformity with a descending analysis, the reflective reports were investigated in the light of a qualitative-interpretative paradigm which enabled us to identify the resources for acting as the predominant dimension, specifically on the individual level, demonstrating the emotions as a starting point for perceptions of realities and capacities for teaching. In the motivational dimension, it was observed the protagonists at PIBID were a significant source of motivation and learning that redefine models for acting, which consolidates a favorable means for professional development when observing others teaching. Intentionally, it was perceived the willingness and desires of the scholars in a sense of always wanting to do their best to gain formative experience as they share personal experiences in the context of the subproject Letras/Inglês